Rancang Bangun Sistem Informasi Online sebagai Media Promosi Trowulan - Rinabi Tanamal; Stephanus Eko Wahyudi (Maranatha University Press, 2016)
Trowulan heritage is a cultural heritage which is one of the relics from the Majapahit Kingdom . A lot of effort has been done by the local community to preserve the culture and engraving surrounding communities. But these efforts have not been maximized,